1957
DOI: 10.2136/sssaj1957.03615995002100010002x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Absorption by Corn Roots as Influenced by Moisture and Aeration

Abstract: Using short-term experiments, the uptake by corn seedlings of Rb 88 from soil and from osmotic solutions has been measured under various levels of moisture stress and oxygen pressure. Soil moisture tensions, up to 12 aim.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1961
1961
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 0 publications
1
16
0
1
Order By: Relevance
“…On the other hand, the soil water content increased in August might lead to an increase of soil nutrient availability (Table 1), and the diffusion coefficient probably increased by reducing the tortuosity of the diffusion path and increasing crosssectional area for diffusion (Barber 1962). The increase of nutrient uptake by plant at higher moisture levels might be possibly due to the thicker moisture films through which the ions diffused (Danielson and Russell 1957).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the soil water content increased in August might lead to an increase of soil nutrient availability (Table 1), and the diffusion coefficient probably increased by reducing the tortuosity of the diffusion path and increasing crosssectional area for diffusion (Barber 1962). The increase of nutrient uptake by plant at higher moisture levels might be possibly due to the thicker moisture films through which the ions diffused (Danielson and Russell 1957).…”
Section: Discussionmentioning
confidence: 99%
“…Two processes of mass-flow in the water absorbed by plant and diffusion of ions were involved, which could act differently across spatial and temporal scales. Factors, such as soil water content (Danielson and Russell 1957;Mederski and Wilson 1960), transpiration ratio (Brouwer 1954), relative extent of root system, concentration gradient at root interface (Barber 1962) and soil texture (Schofield and Graham 1960), could strongly affect the uptake of nutrients by plants.…”
Section: Introductionmentioning
confidence: 99%
“…Fotovat et al (1997) also reported increased amounts of Ca and K in the soil solution by dilution of alkaline soil. Increase in amount of K per pot in the solution of soil above 60% WHC may also Downloaded by [University of California, San Diego] at 22:51 22 August 2015 be caused by increased aqueous diffusion of soil K with higher water content (Place and Barber, 1964;Danielson and Russell, 1957). The much higher concentration of Mn at 100% WHC may be attributed to the dissolution of Mn oxides under reduced conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1409. 3 The following abbreviations will be used: AMP, adenosine monophosphate; ADP Protein accumulated in the seedling during 1 to 6 days of germination and growth ( fig 1C) at a rate similar to the dry-weight increases. Also like the dry-weight changes, a decrease in endosperm-scutellum protein (fig 2B) accompanied the increase in seedling protein.…”
Section: Florida Agricultural Experiments Station Journalmentioning
confidence: 99%
“…
While the influence of sub-optimal water levels on gross aspects of plant growth has been investigated extensively (3,5,6,13,19), little is known about the effect of water stress on metabolic processes. More information on specific effects is needed to establish the influence of environmental-water stress on plant growth and development.
…”
mentioning
confidence: 99%